PENDAMPINGAN PEMBELAJARAN SHOLAT DHUHA BERBASIS EDUKATIF-PARTISIPATIF DALAM PENGUATAN KARAKTER RELIGIUS SISWA SMA MUHAMMADIYAH 2 - Budi Sunariyanto; Abdul Haris; Muh. Zakki Amrulloh; Alan Lutfi Gesang Saputra; Kuni Fatonah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This community service article explains an educational and participatory mentoring program for Dhuha prayer learning at SMA Muhammadiyah 2 Ngawi. The program responded to the partner school need for worship learning that does not stop at routine practice, but also develops conceptual understanding, guided performance, reflective awareness, and sustainable habituation. The mentoring used socialization, material delivery, interactive discussion, guided practice, observation, and participant reflection. The program focused on the meaning, legal basis, time, number of rakaat, procedure, manners, and educational value of Dhuha prayer. The results show that the program strengthened student understanding, improved practice accuracy, and encouraged religious discipline within the school and boarding environment. The activity also produced a practical guide that teachers and students can use for follow-up religious mentoring. The article argues that Dhuha prayer mentoring becomes more effective when schools combine religious culture, teacher assistance, reflective dialogue, and simple evaluation instruments. This community service model can support Islamic education programs that aim to transform routine worship into meaningful character education.